Environmental pollution, a hidden culprit for health issues - Hanqing Xu; Yang Jia; Zhendong Sun; Jiahui Su; Qian S. Liu; Qunfang Zhou; Guibin Jiang (Eco-Environment & Health, 2022)
The environmental and health impacts from the massive discharge of chemicals and subsequent pollution have been gaining increasing public concern. The unintended exposure to different pollutants, such as heavy metals, air pollutants and organic chemicals, may cause diverse deleterious effects on human bodies, resulting in the incidence and progression of different diseases. The article reviewed the outbreak of environmental pollution-related public health emergencies, the epidemiological evidence on certain pollution-correlated health effects, and the pathological studies on specific pollutant exposure. By recalling the notable historical life-threatening disasters incurred by local chemical pollution, the damning evidence was presented to criminate certain pollutants as the main culprit for the given health issues. The epidemiological data on the prevalence of some common diseases revealed a variety of environmental pollutants to blame, such as endocrine-disrupting chemicals (EDCs), fine particulate matters (PMs) and heavy metals. The retrospection of toxicological studies provided illustrative clues for evaluating ambient pollutant-induced health risks. Overall, environmental pollution, as the hidden culprit, should answer for the increasing public health burden, and more efforts are highly encouraged to strive to explore the cause-and-effect relationships through extensive epidemiological and pathological studies.